2010
DOI: 10.5539/gjhs.v2n2p80
|View full text |Cite
|
Sign up to set email alerts
|

Top 7 Issues in Medical Tourism: Challenges, Knowledge Gaps, and Future Directions for Research and Policy Development

Abstract: Medical tourism is a general term that describes patients traveling to obtain health services. The growth of medical tourism is due to a broad range of motivators and increasingly, developing countries are seeking to capitalize on these flows and are linking medical care with actual tourist activities. This commercial linkage between healthcare and tourism is a rapidly developing and profitable industry that is attracting growing interest amongst health researchers. This article summarizes seven leading issues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…However, the majority of existing reports are in the form of news media (Economist, 2008;James, 2009), commentaries or editorials (Budiani-Saberi & Delmonico, 2008;Delmonico, 2009;Jacek, 2012), perspectives, briefs, or conceptual papers (Caballero-Danell & Mugomba, 2007;Heung, Kucukusta, & Song, 2010;Smith & Forgione, 2007), reviews (Behrmann & Smith, 2010;Caballero-Danell & Mugomba, 2007;Carrera & Bridges, 2006;Crooks et al, 2010;George, Henthorne, & Williams, 2010;Heung et al, 2010;Lunt & Carrera, 2010;Lunt et al, , 2012Pennings et al, 2009), and case studies (Kangas, 2010;Moghimehfar & Nasr-Esfahani, 2011;NaRanong & NaRanong, 2011;Schiano & Rhodes, 2010). Relatively few empirical studies have been reported (Blyth, 2010;Canales, Kasiske, & Rosenberg, 2006;Karuppan & Karuppan, 2010Pennings et al, 2009;Satjapot, Johnson, & Garman, 2011;Shenfield et al, 2010;Tsai et al, 2011).…”
mentioning
confidence: 98%
“…However, the majority of existing reports are in the form of news media (Economist, 2008;James, 2009), commentaries or editorials (Budiani-Saberi & Delmonico, 2008;Delmonico, 2009;Jacek, 2012), perspectives, briefs, or conceptual papers (Caballero-Danell & Mugomba, 2007;Heung, Kucukusta, & Song, 2010;Smith & Forgione, 2007), reviews (Behrmann & Smith, 2010;Caballero-Danell & Mugomba, 2007;Carrera & Bridges, 2006;Crooks et al, 2010;George, Henthorne, & Williams, 2010;Heung et al, 2010;Lunt & Carrera, 2010;Lunt et al, , 2012Pennings et al, 2009), and case studies (Kangas, 2010;Moghimehfar & Nasr-Esfahani, 2011;NaRanong & NaRanong, 2011;Schiano & Rhodes, 2010). Relatively few empirical studies have been reported (Blyth, 2010;Canales, Kasiske, & Rosenberg, 2006;Karuppan & Karuppan, 2010Pennings et al, 2009;Satjapot, Johnson, & Garman, 2011;Shenfield et al, 2010;Tsai et al, 2011).…”
mentioning
confidence: 98%
“…Inbound refers to patients coming into a country; outbound refers to patients traveling out of a country. It can also involve travel within the borders of the country, i.e., intrabound or domestic (11,12). But, more commonly, the phrase "medical tourism" is used to describe long-distance travel to another country (13).…”
Section: Literature Review 21 Definitions and Influencesmentioning
confidence: 99%
“…Some companies are in the medical tourism destination (inbound medical tourism companies [IMTC]); others are in the home country of medical tourist (outbound medical tourism companies [OMTC]); however, there are I/OMTC and intrabound MTC, but this article will not discuss them (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). IMTC can easily lead international patients to appropriate medical and traveling services, due to their familiarity with the features and the culture of the destination country and easy access to service providers (10)(11)(12). However, to find health travelers, these companies have to face problems that are more complicated than providing services and require high cost and a lot of time (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as an important transnational actor with broad global authority, the epistemic community has not been reviewed in detail. Accordingly, this paperpresents a history of Britons, and Americans travel to countries such as India, Argentina, Cuba, and Chile [48,49]. Promising "first world health care at third world prices" [48], several Latin American, African, Southeast Asian, and Middle Eastern countries have become regional transplant tourism hubs.…”
Section: Introductionmentioning
confidence: 99%